The Chalcolithic phalanx‑idols of Lapa da Bugalheira (Torres Novas): DOI: https://doi.org/10.5281/zenodo.7920497 - Cardoso, João Luís (2023)
A set of eleven chalcolithic polished first phalanges, ten of which are horse and one domestic ox, transformed into anthropomorphic ideothechnic artifacts is studied. The set was collected in 1941 in a circumscribed space of the neolithic necropolis of the Lapa da Bugalheira cave (Torres Novas). It could originally constitute an altar, organized on one side of the cave and in front of its entrance, or a votive set, related to the ritual or cultual use of the cave. In the same year were collected two phalanges decorated with symbols common to other Chalcolithic ideotechnic artifacts of the Portuguese Extremadura, the Southwest and Southeast of the Iberian Peninsula. They are usually correlated to the Mother Goddess of the agrarian societies of the Mediterranean basin. An inventory of both polished and polished and decorated horse phalanges documented in Portuguese territory up to the present, originating both from funerary spaces and of a domestic nature is also presented.